Effects of urban congestion on safety of networks. Issue 3 (2nd July 2016) - Stempfel, Julie; Guler, S. Ilgin; Menéndez, Mónica; Brucks, Wernher M.
ABSTRACT: The objective of this work is to understand if on urban roads, traffic safety can be linked to traffic congestion. To do so, crash data for the network of Zurich, Switzerland, is linked to traffic data describing congestion from the same network. By aggregating the data, the crash risk in relation to traffic states is analyzed: (1) over the entire network for different times of day and (2) for individual links with different congestion levels. It is found that at the network level, the crash risk (number of crashes per car) is higher during times when the average network speed is lower (5–7 p.m.). Lower speeds are observed during this time period typically due to congestion. Hence, at the network level, there is evidence for congestion being an indicator of increased crash risk. During the same (congested) time period, it is also observed that crashes mostly happen on links with medium speeds, which could be due to higher speed variations within individual links during the congested time periods.